2016
DOI: 10.22319/rmcp.v7i2.4171
|View full text |Cite
|
Sign up to set email alerts
|

Captación de agua de lluvia y retención de humedad edáfica en el establecimiento de buffel (Cenchrus ciliaris L.)

Abstract: Drylands are of high ecological vulnerability due to low vegetative cover and erratic and torrential rainfalls. The aim of this study was to evaluate the use of different sources and rates of soil moisture retainers in the establishment of buffel grass (Cenchrus ciliaris L) in a micro watershade system of rainwater. A randomized block design with three replications was used. Four hydrogel doses: 0, 5, 10 and 15 kg ha -1 and two vermicompost doses: 0 and 40 t ha -1 , were tested. The dose effect of the hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
(6 reference statements)
0
5
0
3
Order By: Relevance
“…Hydrogels offer properties of retention and slow release of water in the soil, either under conditions of immediate or prolonged irrigation, in addition to conserving moisture in the root zone of crops [37]; however, in this study, the properties of the hydrogel were not observed. Other authors highlighted hydrogel applications in buffel grass in arid climates, improved seedling emergence, plant height, dry matter weight and vegetation cover [34]. This positive effect was associated with hydrogels that significantly improved absorption capacity of easily removable water of the soils; although the effectiveness of the gel in improving water retention varies according to the type of soil [38].…”
Section: Moisture Content Of the Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels offer properties of retention and slow release of water in the soil, either under conditions of immediate or prolonged irrigation, in addition to conserving moisture in the root zone of crops [37]; however, in this study, the properties of the hydrogel were not observed. Other authors highlighted hydrogel applications in buffel grass in arid climates, improved seedling emergence, plant height, dry matter weight and vegetation cover [34]. This positive effect was associated with hydrogels that significantly improved absorption capacity of easily removable water of the soils; although the effectiveness of the gel in improving water retention varies according to the type of soil [38].…”
Section: Moisture Content Of the Soilmentioning
confidence: 99%
“…The integration of vegetation covering, as well as the use of moisture retainers, as a way to reduce the high rate of evaporation, key options to be widely adopted. However, so far, they are little explored and hence poorly implemented environment degraded by soil erosion and desertification [34,35].…”
Section: Management Of Grassland: Success Studies In Arid Lands Northmentioning
confidence: 99%
“…In this survey, four dosages of hydrogel were evaluated: 0, 5, 10, and 15 kg ha −1 as well as two compost dosages: 0 and 40 t ha −1 based on dry weight, in the catch system of rainfall water as an experimental unit of 2 m 2 each one. The hydrogel and organic compost were incorporated to the soil manually [27].…”
Section: New Perspectives In Forage Cropsmentioning
confidence: 99%
“…El levantamiento de bordos en curvas a nivel, construcción de mampostería que disminuya la velocidad del agua de lluvia, sistemas de captación de agua de lluvia in situ a base de microcuencas, la resiembra de pastos nativos con métodos de labranza convencional, establecimiento de diferentes especies de plantas nativas o introducidas de potencial forrajero y uso de diferentes tipos de retenedores de la humedad del suelo (9) , son algunas de las tecnologías que se aplican para mitigar el problema de la erosión. La mayor parte de estas técnicas están dirigidas a la retención de la humedad en el suelo ante las altas tasas de evaporación potencial, la cual llega a ser hasta diez veces mayor que la precipitación en zonas semiáridas.…”
Section: Introductionunclassified
“…El pasto buffel (Cenchrus ciliaris L.) es una especie introducida en México que ha mostrado adaptación a condiciones críticas de tipo ambiental en zonas semiáridas, las cuales sustentan en gran medida, su economía en la ganadería extensiva de agostadero (13,14) . Aun cuando esta especie de pasto tiene un alto potencial de adaptación y desarrollo en suelos degradados de zonas semiáridas (9,15) , el establecimiento de esta especie forrajera en condiciones ambientales marginales requiere de un manejo adecuado de los recursos naturales, que garantice su germinación, crecimiento y productividad acorde a su potencial de desarrollo (16,17) . Desde esta perspectiva, las coberturas vegetales en el suelo y otros retenedores de humedad edáfica, entre otras prácticas, están probando ser una estrategia eficaz en el desarrollo sustentable de áreas ganaderas a base de pastizal en suelos degradados de zonas áridas (6,18,19) .…”
Section: Introductionunclassified